On Disturbance Rejection for a Class of Nonlinear Systems - Wei Wei (Complexity)
System control techniques have been developing for a long time. For advanced system requirements, sophisticated control algorithms are necessary for the nonlinear systems with uncertainties and disturbances. Disturbance attenuation or rejection control has been attracting an increasing attention from both control theory researchers and control engineering practitioners. In this paper, a new disturbance rejection control is proposed. Controllable canonical form is taken as the standard form of system dynamics, and a disturbance observer is taken to estimate the discrepancy between system dynamics and its standard form. Then the discrepancy could be compensated by control laws. Conditions of the closed-loop stability and ultimate bound of the tracking error have been obtained. Numerical results have also been presented to support the proposed approach.